Base-promoted cascade radical difluoroalkylation/cyclization of acrylamides for the synthesis of CF2-containing oxindoles and isoquinoline-1, 3-diones. (20th July 2022) - Ma, Shidi; Zhou, Pengsheng; Fan, Xu; Li, Dianjun; Yang, Jinhui
Graphical abstract: Abstract: A base-promoted cascade radical difluoroalkylation/cyclization of acrylamides with ICF2 COOEt to synthesize CF2 -containing oxindoles and isoquinoline-1, 3-diones in moderate to excellent yields was developed under transition metal-free and catalyst-free conditions. This reaction tolerated a variety of functional groups and provided an alternative and mild method for the preparation of difluoroester-substituted five- and six-membered nitrogen-containing heterocyclic products.